The mathematics learning environments of some technical students in Brunei Darussalam - Khalid, Madihah (Education Technology Centre, Universiti Brunei Darussalam, 2003)
The quality of teaching and learning depend considerably on a favorable learning environment. The use of students’ and teachers’ perceptions of their educational environments can assist educators to determine what these groups prefer and thus assist in improving the environment. This can, hopefully, result in more effective teaching and learning conditions and thus improve students’ achievement. In this ongoing study that involves 239 technical students in Brunei Darussalam, a Classroom Environment Survey was developed and administered. The classroom environment survey consists of 56 terms with 8 scales each scales being assessed by 7 items. The qualitative data from this survey and the qualitative data from interviews with teachers and students were analysed and the outcomes of the analyses were used in determining the students’ actual and the preferred environments. This paper reports on the findings from the survey. These results, together with literature review, were used to assist in the design of a suitable instructional model for development of a teaching and learning package formed another bigger study, but this development will not be reported here. [In H. S. Dhindsa, S. B. Lim, P. Achleitner and M. A. Clements, (Eds.). Students in science, mathematics and technical education (pp 192-201). Gadong: Brunei Darussalam, 2003]